Typology of Tri Ning Danu Tourist in Bedugul Tourism Area, Bali - Sunarta, I Nyoman; Sukma Arida, Ni Nyoman; Adikampana, I Made; Karmini, Ni Luh; Nugroho, Saptono (Udayana Journal of Social Sciences and Humanities; Vol 1 No 1 (2017): UJoSSH, Feburary 2017, 2017)
The study aims to find the profile in the form of tourist's typology of the three lakes (Beratan, Buyan and Tamblingan) in Bedugul. Tourist's typology related to the characteristics of the tourism market in Bedugul.This study utilize the survey method to deploy a number of questionnaires. The questionnaires in the form of a structured list of questions to respondents in one time (cross-sectional). The questions posed related to the characteristics of the respondent. Respondents in this study are tourits who travel activities in the three lakes. Respondents were determined using non-probability sampling (purposive sampling). Intake of sample based on certain criteria. The criteria based on the judgment or a certain quota specific. Selection of respondents in this study is based on a particular consideration to the purpose of research that tourists visiting the three lakes. The number of samples taken as many as 200 tourists. The number of respondents that are larger than 100 makes it possible to do statistical analysis. The results showed tourist's typology based on the characteristics of tourism market varied in the three lakes. There is also a similarity pattern in each lake typology related tourists visiting that want to enjoy nature and culture based tourist attractions, first timer tourist, and day visitors, tourist spending levels are relatively low, under IDR 500.000.